Diskursus Hermeneutika Media Sosial: Analisis Wacana Kritis Akun Instagram @elmaslak dan @tanwirid - usman, muh ilham; Junaedi, Muhammad Edy (Tasamuh: Jurnal Studi Islam, 2024)
Abstract Confrontation about the use of hermeneutics in the interpretation of the Qur'an is still hot among Qur'an scholars today. The confrontation also colors the social media platform which is now an instrument to convey one's views or ideas. The pro-contra response to the hermeneutics of the Qur'an appears on the Instagram accounts @elmaslak and @tanwirid which are different in viewing the interpretation of the Qur'an with hermeneutical nuances. This research was also conducted to determine the response of the two accounts, through the question of how the two accounts respond to hermeneutics in the interpretation of the Qur'an. In answering this question, this research was compiled using a qualitative approach and using Teun A. Van Dijk's critical discourse analysis theory. This research also shows that the varied responses to hermeneutics are due to differences in the scientific genealogy of the two account owners. The @elmaslak account, which is affiliated with al-Azhar Cairo alumni, gives a response that tends to reject hermeneutics. While @tanwirid, which is affiliated with students of al-Qur'an and tafsir in Indonesia, tends to be open in viewing hermeneutics in the interpretation of the Qur'an. The difference in response certainly provides its own color in the scholarship of al-Qur'an and tafsir. With this research, it indicates that the geneology of tafsir studies has experienced a dialectic of study products, not only limited to written texts but massively produced on social media whose readers are no longer exclusive. Keywords: Hermeneutics, Social Media, @elmaslak, @tanwirid